Recruitment And Selection of Head Department (In West Java Province's Government of Indonesia) (Proceedings of the International Conference on Social Sciences, 2020)
This article reviews research on Recruitment and Selection of the Head of Department (in West Java Province's Government of Indonesia). This article shows the topic related to recruitment and selection of heads of departments in the staffing of the regional government of West Java Province. Indonesian Government Management of State Civil Service explains that the State Civil Service (ASN) policies and management are based on qualifications, competencies, and performance are fair and reasonable regardless of political background, race, colour, origin, gender, marital status, age or disability condition. The policy of filling in the High Leadership Position (JPT) through open selection has been widely implemented, to obtain state civil apparatus that have good qualifications, competencies and performance as a condition for occupying certain positions. This research uses taken mixed methodology instead of and takes the theory of merit systems and Government Regulation Management of Civil Servants. Opportunities for Civil Servants women to participate in the selection of Structural Position, where these terms are the recruitment of a merit system, which provides opportunities to candidates from internal and external organizations, organizational goals for getting competent employees can be implemented. Recruitment and Selection of the Head Department. The results showed that the recruitment was well carried out and made several changes in a positive direction including elected officials, minimizing the direct engagement made by regional heads, and concluded with this recruitment and selection research can be continued in the future. although slow and sometimes complicated, the general method used is open selection is meritocratic.
Keywords: Government; Recruitment; Open Selection